Geological and geochronological relationships of the Thompson nickel belt, Manitoba - Cranstone, Donald A.; Turek, Andrew (Canadian Journal of Earth Sciences, 1976)
The Pikwitonei province is an early Precambrian inlier of retrograded granulite and amphibolite facies gneisses that separates the Superior and Churchill provinces in Manitoba. The granulites are unconformably overlain by rocks of the Superior province along the southeast boundary, and are in contact with rocks of the Wabowden subprovince to the northwest. Whole rock Rb–Sr isochron analyses for the Wabowden migmatitic gneisses give an age of 2820 ± 135 m.y. ( 87 Rb decay constant = 1.39 × 10 −11 y −1 ). We interpret this age as representing the formation of these migmatitic gneisses by remobilization of the Pikwitonei basement either during an early stage of the Kenoran orogeny or during an orogeny earlier than the Kenoran. An additional two samples of the migmatitic gneiss give an age of 1720 m.y., which reflects updating by the Hudsonian orogeny. Similarly, whole-rock Rb–Sr analyses for an argillaceous metasedimentary rock in the Wabowden subprovince yield an age of 1640 ± 170 m.y. It is postulated that the metasedimentary and metavolcanic members of the Wabowden subprovince were deposited on, and infolded with, the migmatitic gneisses.Granitic rocks belonging to the Churchill province yield typically Hudsonian ages. A pink quartz monzonite gives an age of 1730 ± 90 m.y., while an augen quartz monzonite gives an age of 1805 ± 190 m.y. Both plutons have low initial ratios, that are, however, significantly distinct at the 5% level. Churchill province sedimentary rocks yield an age of 1975 ± 155 m.y. This age may simply be a Hudsonian overprinting or it may be the age of deposition, in which case it places a maximum age for the Setting Lake – Assean Lake fault in the area. A minimum age for one branch of the fault, is 1806 m.y. This is the age of a post-cataclastic pegmatite dyke.